1983
DOI: 10.1002/pssa.2210750130
|View full text |Cite
|
Sign up to set email alerts
|

Thermoluminescence of Z centres in LiF (TLD-100) at elevated irradiation temperatures

Abstract: Elevated irradiation temperature studies with LiF phosphor and a critical review of the Z centre model of Nink and Kos reveal that the correlation in the intensity rise of the 285 °C peak (peak 7) and Z3 band at Tirr = 215 °C reported by Gartia is a consequence of the increase in the TL intensity of peak 10 (≈ 400 °C). The correlation in the TL intensities of peaks 7 and 10 is anticipated because these two peaks arise due to the thermal ionization of Z2 and Z3 centres, respectively. A review of the various exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1985
1985
1993
1993

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Whether Mg directly captures electrons or whether just perturbs the electron centres, characteristic of the host lattice, is to be decided. Several papers (Mort 1965;Nink and Kos 1976;Parfianovich et al 1976;Nink 1977a, b,c,d, 1979, 80;Mehta et al 1977;Kos and Mieke 1978;Kos and Takeuchi 1980;Rao 1980;Jain 1981c;Lakshmanan et al 1983) support the latter view. The idea ofZ centres of Mg started with the suggestion (Mort 1965;Mort and Zimmerman 1966) that the empirical Mollow-Ivey relation for Z 3 centres in alkali halides predicts the Z3 band in LiF:Mg at 225nj.…”
Section: Lif-tlo 100mentioning
confidence: 99%
See 1 more Smart Citation
“…Whether Mg directly captures electrons or whether just perturbs the electron centres, characteristic of the host lattice, is to be decided. Several papers (Mort 1965;Nink and Kos 1976;Parfianovich et al 1976;Nink 1977a, b,c,d, 1979, 80;Mehta et al 1977;Kos and Mieke 1978;Kos and Takeuchi 1980;Rao 1980;Jain 1981c;Lakshmanan et al 1983) support the latter view. The idea ofZ centres of Mg started with the suggestion (Mort 1965;Mort and Zimmerman 1966) that the empirical Mollow-Ivey relation for Z 3 centres in alkali halides predicts the Z3 band in LiF:Mg at 225nj.…”
Section: Lif-tlo 100mentioning
confidence: 99%
“…In later work, a correlation between 285 C peak and 225 nm band was attempted (Gartia 1977;Kos and Nink 1979), but Bapat and Kathuria (1981) and Jain (1981 c) have shown that the 225 nm band is not totally annealed out during 285 C peak, it vanishes only after 400 C; and hence the earlier assignment is correct. In recent years, the 285 C peak has been correlated with the 310 nm band (Lakshmanan et al 1982a(Lakshmanan et al , 1983Chandra et al 1982a).…”
Section: Lif-rto 100mentioning
confidence: 99%